„Inny” w klasie szkolnej - Muszyńska, Ewa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
The article features a description and an analysis of the ‘other’ in the classroom – i.e. a student who differs (significantly) from their peers through, for example, a distinct personality trait, behavior, looks, background or religion. It also demonstrates how a classroom and the ‘other’, function in terms of their mutual dependencies. Finally, the article discusses effective educational methods designed for a classroom, where the ‘other’ is present.